Sources of corporate income tax compliance costs: The case of Malaysian self-assessment system - Sapiei, N.S.; Abdullah, M. (2014)
This study identifies the sources of income tax work for corporate taxpayers under the Self-Assessment System (SAS) environment. Utilizing the researcher administered survey, the sources of tax compliance costs is investigated. The internal external costs ratio was 37:63, indicating that there is a heavy reliance on external sources. This study therefore concluded that tax compliance activities were mainly handled by external tax professionals. Comparative findings with existing studies provide further contributions to corporate tax knowledge, tax administration and practices.